O enfrentamento do analfabetismo de mulheres velhas no município de Castanhal, na Amazônia Paraense: a velhice negada e a educação “garantida” - FALCÃO, Ildete da Silva (Universidade Federal do Pará, 2020)
The confrontation of the illiteracy of old women in the Municipality of Castanhal, in the Paraense Amazon, was the object of this research, when it aroused in us the problematization and the will to investigate this phenomenon, for the much that it excludes in this region, particularly in Castanhal, in the State of Pará, where the Campus of the Federal University of Pará (UFPA) is located, which, through university extension, develops the program Education Group in the Third Age (GETI), the locus of this research. The study was carried out with 12 subjects, students and former students of the 2nd stage classes of Youth and Adult Education (EJA), resulting from the partnership between the Campus and the Municipal Education Department (SEMED), aiming to investigate the determining factors for the confrontation of illiteracy by the old women who attend the GETI program. As a researcher, teacher and old woman, our interest in the study was of a theoretical, political and existential nature. In this sense, we conducted a qualitative-exploratory field research, which forged some methodological procedures, namely: the bibliographical survey, with the reading of the theoretical ones on the subject, immersion in the program file GETI and the necessary listening of subjects through semi-structured interviews. To analyze the interview data we use Content Analysis, based on Bardin (2016) and Franco (2018). The study revealed the situation of socioeconomic and cultural prejudice of the old women investigated, as a consequence of the long period of life in illiteracy or low level of schooling. It also evidenced the protagonism when overcoming this condition by revealing attitudes of independence and autonomy acquired by the literacy process. It is also pointed out that current educational systems are not prepared to meet the specificities of the elderly, which requires the government to implement legal determinations concerning the right of the elderly with adequate physical and pedagogical structure in the sense of ensuring that these citizens are welcomed with physical and emotional security through critical, dialogic and respectful pedagogical interventions, in a perspective of providing meaningful learning throughout life.